HEMATOLOGY OF STRIPED CATFISH (Pangasianodon hypophthalmus) FED WITH ADDED FERMENTED HERBAL MEDICINE AND TESTED WITH Aeromonas hydrophila - Rizvi, Fharisa Nabila; Syawal, Henni; Riauwaty, Morina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Fermented herbs made from turmeric, ginger, and kencur have the potential to be antimicrobials and immunostimulants that can increase appetite and reduce fish stress due to changes in water quality. The research was conducted from June 2024 to August 2024 at the Fish Disease and Parasite Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study aims to determine the best frequency of fermented herbs enriched on the health of striped catfish (Pangasianodon hypophthalmus) hematology after challenge with Aeromonas hydrophila. The research method used a completely randomized design (CRD) with one factor, five treatments, and three replicates. Treatments consisted of Kn (negative control, no challenge test), Kp (positive control and challenge test), P1 (herbs enriched every day and challenge test), P2 (giving every 3 days and test challenge), and P3 (giving every 5 days and a test challenge). Fish were kept for 46 days and challenged with A. hydrophila (10⁸ CFU/mL) on day 32. Clinical symptoms were observed for 14 days post-challenge. The best results were obtained in treatment P1 with the following hematological parameters: erythrocytes 2.37×10⁶ cells/mm³, hematocrit 36.00%, hemoglobin 9.60 g/dL, leukocytes 11.14×10⁴ cells/mm³, glucose 69.33 mg/dL, and normal leukocyte differentiation. The survival rate reached 100%. Feeding fermented herbs effectively improved the health and body endurance of striped catfish